ANALISIS AKTIVITAS PERLINDUNGAN SINAR UV SARI BUAH SIRSAK (Annona muricata L.) BERDASARKAN NILAI SUN PROTECTION FACTOR (SPF) SECARA SPEKTROFOTOMETRI UV-VIS - Rahmawati Rahmawati; A. Muflihunna; Meigita Amalia (Faculty of Pharmacy, Universitas Muslim Indonesia, 2018)
Sunlight contains UV rays that adversely affect the skin. These adverse effects can be minimized by the use of UV protective materials, both natural and synthetic. Soursop fruit (Annona muricata L.) has a high content of polyphenol compounds, some vitamins such as vitamin C, B1 and B2. This study aims to determine the activity of UV light protection on soursop juice (Annona muricata L.) by using Sun Protection Factor (SPF) calculation. The measurement of SPF values using the UV-Vis spectrophotometric method in the wavelength range from 290-320 nm. The results showed that soursop juice (Annona muricata L.) had UV light protection activity at 1% concentration of 5,188, 3% concentration of 12.242 and 5% concentration of 17,247. The category of SPF values in a row that is medium, maximum and ultra